Pest Management Perceptions and Practices for Equine Farms in North and Central Florida - Erika T. Machtinger; Norman C. Leppla; Cindy Saunders (EDIS)
Equine facilities have unique pest management problems due to facility structure and horse husbandry practices. In Florida, homes on small equine farms are generally located in close proximity to pastures, stalls or run-in sheds, manure piles, and other fly breeding habitats. So, homeowners have a high risk of exposure to pathogens that can be transmitted by filth flies to humans. Integrated pest management for equine farms requires accurate diagnosis of pest problems and the coordinated use of science-based management practices, but a recent survey shows that many equine property owners don’t know enough about the identification, biology, and presence of filth fly pests on their properties to develop successful IPM programs. This 7-page fact sheet was written by Erika T. Machtinger, Norman C. Leppla, and Cindy Saunders, and published by the UF Department of Entomology and Nematology, March 2013.